Analisis Disiplin Kerja Pegawai Kantor Dinas Sosial Tenaga Kerja Dan Transmigrasi Kabupaten Sarolangun Pada Tahun 2014 - Ilpa Nilawati (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
Discipline is very important in this life. Self-discipline is a habit cycle that we do repeatedly and continuously irrationally so that it becomes something we usually do. As far as the field research that the author did, it can be seen in the Office of Social Labor and Transmigration of the Sarolangun Regency that there is still low work discipline possessed by the employees of the Office of Manpower and Transmigration. . The approach that the author uses in this study is a quantitative approach, namely analyzing the work discipline of employees at the Social Service Office for Labor and Transmigration in Sarolangun Regency. The data collection method consists of: 1. Library research, 2. Field research which includes 3 methods, namely: a. Questionnaire, b. Interview, c. Documentation. The results of this study conclude that the condition of employee discipline at the Social Service Office for Manpower and Transmigration in Sarolangun Regency still needs serious attention from the leaders of the office, so that in the future it will improve in a better direction.